RaPiD: A toolkit for reliability analysis of non-deterministic systems - GUI, Lin (Institutional Knowledge at Singapore Management University, 2014)
Non-determinism in concurrent or distributed software systems (i.e., various possible execution orders among different distributed components) presents new challenges to the existing reliability analysis methods based on Markov chains. In this work, we present a toolkit RaPiD for the reliability analysis of non-deterministic systems. Taking Markov decision process as reliability model, RaPiD can help in the analysis of three fundamental and rewarding aspects regarding software reliability. First, to have reliability assurance on a system, RaPiD can synthesize the overall system reliability given the reliability values of system components. Second, given a requirement on the overall system reliability, RaPiD can distribute the reliability requirement to each component. Lastly, RaPiD can identify the component that affects the system reliability most significantly. RaPiD has been applied to analyze several real-world systems including a financial stock trading system, a proton therapy control system and an ambient assisted living room system.